2016
DOI: 10.1002/2015ja022140
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of proton pitch angle distributions measured by the Radiation Belt Storm Probes Ion Composition Experiment

Abstract: A statistical study of ring current‐energy proton pitch angle distributions (PADs) in Earth's inner magnetosphere is reported here. The data are from the Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) on board the Van Allen Probe B spacecraft from 1 January 2013 to 15 April 2015. By fitting the data to the functional form sinnα, where α is the proton pitch angle, we examine proton PADs at the energies 50, 100, 180, 328, and 488 keV in the L shell range from L = 2.5 to L = 6. Three PAD types a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In contrast to symmetric isotropic (T ‖ = T ⊥ = 16 keV ≡ T 0 ) PSD with loss cones case in Yamakawa et al (2019), the initial PSD is the butterfly distribution with asymmetry in pitch angle direction. Butterfly distribution has been reported by previous in situ spacecraft observations (e.g., Shi et al, 2016). We add the asymmetry of the PSD since the drift-bounce resonance excitation of ULF waves is not found if we put symmetric butterfly distribution.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 82%
“…In contrast to symmetric isotropic (T ‖ = T ⊥ = 16 keV ≡ T 0 ) PSD with loss cones case in Yamakawa et al (2019), the initial PSD is the butterfly distribution with asymmetry in pitch angle direction. Butterfly distribution has been reported by previous in situ spacecraft observations (e.g., Shi et al, 2016). We add the asymmetry of the PSD since the drift-bounce resonance excitation of ULF waves is not found if we put symmetric butterfly distribution.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 82%
“…This means that the measured particle flux and pressure becomes smaller as the MLAT of a satellite increases. The pancake distribution is often modeled by the function sinγα (e.g., Shi et al, ; Summers & Shi, ), where γ is a power index to show the plasma anisotropy. According to the theory of field‐aligned particle distribution in static equilibrium (Parker, ), when the pitch angle distribution can be expressed by sinγα, the particle flux decreases with false[Bfalse/Beqfalse]γ12 along the field line, where B / B eq is the magnetic strength normalized by its value at the magnetic equator.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several surveys (e.g., Denton et al, ; Sarno‐Smith et al ; Shi et al, ; Zhao et al, ) focusing on the plasma PADs based on Van Allen Probes observations. For example, Denton et al () used the Helium, Oxygen, Proton, and Electron (HOPE) instrument on board Van Allen Probes as well as the Magnetospheric Plasma Analyzer (MPA) on board Los Alamos National Laboratory (LANL) satellites to study the PADs of 30 eV to 1 keV electrons at different L shells and magnetic local times (MLTs) for both quiet and geomagnetically active periods.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that there is a strong depletion of the H + ions at PA near 90°, while PA near 0° and 180° remain nearly constant. Shi et al () have examined H + PADs at energies from 50 to 488 keV in the L shell range from L = 2.5 to L = 6 based on Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) on board the Van Allen Probe B spacecraft from 1 January 2013 to 15 April 2015. Three PAD types including pancake, butterfly (i.e., having a flux peak somewhere between 90° and 0° as well as 90° and 180°), and isotropic are identified in different energies, MLTs, and L shells, and the MLT dependence of these proton PADs became more distinct with increasing particle energy.…”
Section: Introductionmentioning
confidence: 99%